Transforming the Healing Spaces: Exploring the Impact of Interior Design on Art Therapy Rooms - Diya Chawla; Deepti Pande Rana (International Journal of Behavioral Sciences, 2024)
Art Therapy is one of the widely used therapeutic methodologies in psychology with the motive of dealing and eliminating a person’s anxious thoughts or emotions by teaching them how they can cope with their cognitive conditions. However, it is often noted that the clinical environment this procedure takes place in may hinder with the proper development of a patient’s mental health. Therefore, an art therapy clinic should be designed in a manner that promotes and encourages proper shaping of a patient’s cognitive state by indulging in less clinical-like environment situations. This research paper studies the necessary impact of interior design in order to create healing spaces such as the art therapy rooms that engages in user-friendly and functional designs, ensuring the well-being of patients. This paper therefore delves into the specific strategies that can be employed to optimize art therapy environments for enhanced patient outcomes through comprehensive literature reviews and analysis that investigates various elements of interior spaces such as lighting, air ventilation, colour psychology, furniture layouts, use of artificial and natural materials and so on, required for art therapy sessions and activities that would create a healthy, safe and intriguing experience for the users. This paper thus aims at providing valuable insights and recommendations for interior designers, architects and healthcare professionals dealing in such therapeutic settings for the creation of enhanced healing spaces that would positively impact the holistic care of the patients, promising a healthy recovery by undergoing and transforming the therapy sessions in a fun environment.
Keywords: Environment Psychology; Interior of Art Therapy Spaces; Stress Reducing Interior Spaces; and Color Psychology; interior design